Inovasi Pembelajaran Pendidikan Kewarganegaraan: Pengembangan Media Pembelajaran Google Sites dan Aplikasi Android Untuk Mahasiswa - Al Fikri, Muhammad Arif (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
The purpose of the study was to develop Google Sites and Android applications and to find out the responses of FTIK UIN Salatiga students in learning Citizenship. The development research used the ADDIE model through 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at FTIK UIN Salatiga. Development through the analysis stage consists of needs analysis and material scope. The design stage involves making flowcharts and storyboards. The development stage is collecting materials and producing Google sites and Android applications called